Perhitungan Kebutuhan Listrik Pada Pembangkit Listrik Tenaga Biogas (PLTBG) Menggunakan Limbah Cair Pada Pabrik Kelapa Sawit PT. Ramajaya Pramukti - Dasril Dasril; Suwitno Suwitno; Noveri Lysbetti Marpaung (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Pome is one of liquid waste from palm oil mill. There’s quite big amount of this waste which can be converted to a biogas and used as an electrical energy source. In this research, we conduct a survey to ultilization POME use as a raw material for biogas power plant at pt ramajaya pramukti which is located in kampar regency riau province. pt ramajaya pramukti is a palm oil mill that has a palm oil production capacity of 60 ton / hour. Type of data used in this analysis is a secondary data which includes FFB data and the discahrge of waste produced by the factory itself. In january 2017 PT.Ramajaya Pramukti process 20,722.799 ton of FFB and produce 11,056 m3 of pome. The lowest ffb processing is occured in june 12,363.807 ton which produce 7,079 m3 of pome. This result of pome utilization potential in pt ramajaya promukti is used as a raw material for biogas power plant which generate electricity as big as 4.09 mwh in January 2017 and 2.12 mwh in june 2017.. Key words: PLTBg, POME, Electricity Palm Oil Mil